Reactivity studies of pincer bis-protic N-heterocyclic carbene complexes of platinum and palladium under basic conditions - Marelius, David C.; Moore, Curtis E.; Rheingold, Arnold L.; Grotjahn, Douglas B. (Beilstein Journal of Organic Chemistry, 2016)
Bis-protic N-heterocyclic carbene complexes of platinum and palladium (4) yield dimeric structures 6 when treated with sodium tert-butoxide in CH2Cl2. The use of a more polar solvent (THF) and a strong base (LiN(iPr)2) gave the lithium chloride adducts monobasic complex 7 or analogous dibasic complex 8.
Keywords: NHC; 15N NMR spectroscopy; palladium; platinum; protic N-heterocyclic carbene

(untitled) - Hermann, W. A. (Angew. Chem., Int. Ed., 2002)

(untitled) - Díez-González, S.; Marion, N.; Nolan, S. P. (Chem. Rev., 2009)

(untitled) - Hopkinson, M. N.; Richter, C.; Schedler, M.; Glorius, F. (Nature, 2014)

(untitled) - Kuwata, S.; Ikariya, T. (Chem. – Eur. J., 2011)

(untitled) - Hahn, F. E. (ChemCatChem, 2013)

(untitled) - Zhao, B.; Han, Z.; Ding, K. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kuwata, S.; Ikariya, T. (Chem. Commun., 2014)

(untitled) - Jahnke, M. C.; Hahn, F. E. (Coord. Chem. Rev., 2015)

(untitled) - Isobe, K.; Kai, E.; Nakamura, Y.; Nishimoto, K.; Miwa, T.; Kawaguchi, S.; Kinoshita, K.; Nakatsu, K. (J. Am. Chem. Soc., 1980)

(untitled) - Isobe, K.; Kawaguchi, S. (Heterocycles, 1981)

(untitled) - Flowers, S. E.; Cossairt, B. M. (Organometallics, 2014)

(untitled) - Miranda-Soto, V.; Grotjahn, D. B.; DiPasquale, A. G.; Rheingold, A. L. (J. Am. Chem. Soc., 2008)

(untitled) - Miranda-Soto, V.; Grotjahn, D. B.; Cooksy, A. L.; Golen, J. A.; Moore, C. E.; Rheingold, A. L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Marelius, D. C.; Darrow, E. H.; Moore, C. E.; Golen, J. A.; Rheingold, A. L.; Grotjahn, D. B. (Chem. – Eur. J., 2015)

(untitled) - Seyboldt, A.; Wucher, B.; Hohnstein, S.; Eichele, K.; Rominger, F.; Törnroos, K. W.; Kunz, D. (Organometallics, 2015)

(untitled) - Moser, M.; Wucher, B.; Kunz, D.; Rominger, F. (Organometallics, 2007)

(untitled) - Helm, L.; Merbach, A. E. (Chem. Rev., 2005)